2021
DOI: 10.1007/s00011-021-01456-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of alpha-1-antitrypsin deficiency with vitamin D status: who is most at risk of getting severe COVID-19?

Abstract: Introduction Coronavirus disease 2019 (COVID-19), a new disease that we do not know yet how to treat, is rapidly evolving and has forced us to stay indoors. Surprisingly, a broad range of symptoms has been reported since COVID-19 emergence. Individual variations in susceptibility to SARS-CoV-2 can be due to non-genetic and genetic factors. Alpha-1-antitrypsin deficiency (AATD) is an inherited condition that is associated with an increased risk of liver and lung diseases which may increase susceptibility to COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Shimi et al hypothesized that low vitamin D levels in patients with COVID-19 could result in acquired AATD, leading to greater clinical severity and a higher risk of death [ 74 ].…”
Section: Shared Pathogenic Pathwaysmentioning
confidence: 99%
“…Shimi et al hypothesized that low vitamin D levels in patients with COVID-19 could result in acquired AATD, leading to greater clinical severity and a higher risk of death [ 74 ].…”
Section: Shared Pathogenic Pathwaysmentioning
confidence: 99%
“…Interestingly, when AAT and glucocorticoid are combined in macrophages, lower glucocorticoid concentrations used allowed up-regulation of IL-1Ra, whereas higher glucocorticoid levels antagonized the effects of AAT [ 112 ]. Vitamin D deficiency may also lead to decreased release of AAT from T cells, causing decreased release of the anti-inflammatory cytokine IL-10 [ 115 , 116 ]. Tumpara et al [ 117 ] showed that recombinant AAT (made in Chinese hamster ovary cells) was more potent than plasma-derived AAT in inhibiting pro-inflammatory cytokine production from peripheral blood mononuclear cells stimulated with both lipopolysaccharide and spike proteins.…”
Section: Other Activities Of Aat Could Mitigate Severity Of Covid-19mentioning
confidence: 99%
“…Thirdly, people with certain respiratory diseases, may be at a higher risk of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection and/or developing severe respiratory complications [3][4][5][6], which may discourage them from trial participation. Early stage trials investigate safety, tolerability and PK of new drug candidates, formulations and routes of administration and explore pharmacological effects and potential drug interactions.…”
Section: Short Communicationmentioning
confidence: 99%